Thematic Platform in vitro Diagnostics Technological Progress with a Powerful Network - Elsbeth Heinzelmann (CHIMIA, 2016)
In vitro diagnostics (IVD) has huge potential. Primary drivers in the global market are the patient's awareness of infectious diseases, the introduction of advanced molecular and tissue diagnostic tests for patient-stratified and targeted anti-cancer therapy and, last but not least, the growing geriatric population. Rapid progress in device miniaturization and information technology (IT) offers new possibilities in decentralized testing. Grand View Research Inc. expects the global market for IVD to reach US $ 74.3 billion by 2020. Hence the launch in 2015 by the NTN Swiss Biotech – together with the driving forces of Biotechnet Switzerland – of the 'Thematic Platform in vitro Diagnostics'.